PGC-1α activity in nigral dopamine neurons determines vulnerability to α-synuclein - Ciron, Carine (Acta Neuropathol Commun, 2015)
INTRODUCTION: Mitochondrial dysfunction and oxidative stress are critical factors in the pathogenesis of age-dependent neurodegenerative diseases. PGC-1α, a master regulator of mitochondrial biogenesis and cellular antioxidant defense, has emerged as a possible therapeutic target for Parkinson’s disease, with important roles in the function and survival of dopaminergic neurons in the substantia nigra. The objective of this study is to determine if the loss of PGC-1α activity contributes to α-synuclein-induced degeneration. RESULTS: We explore the vulnerability of PGC-1α null mice to the accumulation of human α-synuclein in nigral neurons, and assess the neuroprotective effect of AAV-mediated PGC-1α expression in this experimental model. Using neuronal cultures derived from these mice, mitochondrial respiration and production of reactive oxygen species are assessed in conditions of human α-synuclein overexpression. We find ultrastructural evidence for abnormal mitochondria and fragmented endoplasmic reticulum in the nigral dopaminergic neurons of PGC-1α null mice. Furthermore, PGC-1α null nigral neurons are more prone to degenerate following overexpression of human α-synuclein, an effect more apparent in male mice. PGC-1α overexpression restores mitochondrial morphology, oxidative stress detoxification and basal respiration, which is consistent with the observed neuroprotection against α-synuclein toxicity in male PGC-1α null mice. CONCLUSIONS: Altogether, our results highlight an important role for PGC-1α in controlling the mitochondrial function of nigral neurons accumulating α-synuclein, which may be critical for gender-dependent vulnerability to Parkinson’s disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40478-015-0200-8) contains supplementary material, which is available to authorized users.